Industrial training report: W Tech Media Sdn Bhd - Ridzuan, A’isyah (Universiti Teknologi MARA, Perlis, 2024)
My internship at W Tech Media Sdn Bhd from March 4, 2024, to August 9, 2024, was an invaluable experience that provided comprehensive exposure to the dynamic field of social media marketing. W Tech Media is a leading social media marketing agency renowned for its innovative and tailored digital marketing solutions. Specializing in platforms like TikTok, the agency helps businesses enhance their online presence, drive engagement, and boost conversions through compelling content and strategic campaigns. With a diverse client base across various industries, W Tech Media leverages its expertise in digital trends and data analytics to deliver impactful results. Known for its adaptability, customized strategies, and proven track record, W Tech Media is a trusted partner for businesses seeking to maximize their digital marketing efforts. I was actively involved in several key projects and responsibilities that significantly enhanced my skills and understanding of the industry. During my time there, I was entrusted with the launch of special projects, specifically handling the "Whitebox TikTok Marketing Agency" initiative from ideation to publication. This involved shooting photos and videos for social media content, ensuring high-quality visuals that met client specifications. I assisted in setting up studios and lighting to create optimal shooting conditions, contributing to the overall production process. Participating in ideation sessions, I helped generate creative ideas for content creation, followed video storyboards, and adhered to the director’s instructions to capture the required shots. Additionally, I adhered to established workflows and systems with meticulous attention to detail, contributing to the agency's efficiency and productivity. This hands-on experience allowed me to develop a robust understanding of the operational aspects of a social media marketing agency, from content creation and editing to project management and client relations. The SWOT analysis of W Tech Media reveals its strengths in having a positive working environment, a focus on self-growth, and a strong demand for its social media marketing services, particularly on TikTok. Weaknesses include resource constraints such as limited funding, manpower, and technological infrastructure. Opportunities lie in expanding service offerings, leveraging new digital marketing trends, and increasing market reach. However, threats include intense competition, rapidly changing digital landscapes, and economic fluctuations that could impact client budgets. This analysis underscores the need for strategic planning to capitalize on strengths and opportunities while addressing weaknesses and mitigating threats. Overall, my internship at W Tech Media was a period of significant professional growth. The experience honed my creative and technical skills, provided insight into industry best practices, and prepared me for future endeavors in the field of digital marketing.